1989
DOI: 10.1152/jappl.1989.67.6.2212
|View full text |Cite
|
Sign up to set email alerts
|

Flow and volume dependence of respiratory mechanical properties studied by forced oscillation

Abstract: The influence of inspiratory and expiratory flow magnitude, lung volume, and lung volume history on respiratory system properties was studied by measuring transfer impedances (4-30 Hz) in seven normal subjects during various constant flow maneuvers. The measured impedances were analyzed with a six-coefficient model including airway resistance (Raw) and inertance (Iaw), tissue resistance (Rti), inertance (Iti), and compliance (Cti), and alveolar gas compressibility. Increasing respiratory flow from 0.1 to 0.4 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 0 publications
3
20
0
Order By: Relevance
“…2) which, analysed with equation 6, corresponded mostly to negative flow dependence (table 3). This finding is in agreement with the observations of OOSTVEEN et al [21] who derived Iaw from 4-30 Hz Ztr data obtained during constant-flow inspiratory and expiratory manoeuvres. During inspiration Iaw decreased from 2.12 Pa·s 2 ·L -1 at 0.1 L·s -1 to 1.79 hPa·s 2 ·L -1 at 0.4 L·s -1 ; the changes, however, were smaller during the expiratory phase (2.15 and 1.91 Pa·s 2 ·L -1 at 0.1 and 0.4 L·s -1 , respectively), which is at variance with the present observations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2) which, analysed with equation 6, corresponded mostly to negative flow dependence (table 3). This finding is in agreement with the observations of OOSTVEEN et al [21] who derived Iaw from 4-30 Hz Ztr data obtained during constant-flow inspiratory and expiratory manoeuvres. During inspiration Iaw decreased from 2.12 Pa·s 2 ·L -1 at 0.1 L·s -1 to 1.79 hPa·s 2 ·L -1 at 0.4 L·s -1 ; the changes, however, were smaller during the expiratory phase (2.15 and 1.91 Pa·s 2 ·L -1 at 0.1 and 0.4 L·s -1 , respectively), which is at variance with the present observations.…”
Section: Discussionsupporting
confidence: 93%
“…In another work from the same laboratory [18] The analysis revealed some negative volume dependence of Raw, which is consistent with previous data. OOST-VEEN et al [21] reported a decrease with volume of airway resistance derived from transfer impedance during inspiratory manoeuvres. PESLIN et al [18] reported values of K 3 ranging from about -0.3 to -0.7 for inspiration and -0.8 to -1.4 hPa·s·L -2 for expiration.…”
Section: Discussionmentioning
confidence: 99%
“…6), the analysis showed the expected effect, namely, a marked decrease in Xti at all frequencies, corresponding to a large increase of Eti. Interestingly, Xaw was almost unchanged, although it represented at low frequencies only a small part of the total reactance; this is in agreement with observations showing that Iaw varies little with lung volume (17) and strongly supports a very good separation between the two components. Elastic loading also significantly increased Raw, which is consistent with the decreased TGV.…”
supporting
confidence: 89%
“…Commensurate with these rising flows was a timedependent increase in pulmonary resistance (i.e., RL,I and RL,E) over the V O 2sc phase, exacerbating the amount of resistive work expended per breath. The increase in RL,I during severe work rate transitions was probably due to a flow-dependent phenomenon, which may be attributed to the development of turbulent flow within larger-diameter airways (3,29). The increase in RL,E over the V O 2sc phase, on the other hand, was likely the result of a greater mechanical constraint on breathing during severe cycling trials, namely, the development of EFL.…”
Section: Discussionmentioning
confidence: 95%